CFD-моделювання процесу піролізного високотемпературного розкладання сировини рослинного походження у побутових твердопаливних котлах - Галдінов, Михайло Васильович; Пешко, Віталій Анатолійович; Риндюк, Дмитро Вікторович; Черноусенко, Ольга Юріївна; Лементар, Святослав Юрійович (My University, 2018)
У статті проведено моделювання процесу розкладання та горіння рослинної сировини у твердопаливному піролізному побутовому котлі (ТППК), оскільки використання нетрадиційних і відновлюваних джерел енергії є доцільним для енергетики України. Показано, що ефективність ТППК значною мірою залежить від його режимних і конструкційних параметрів. Відмічені переваги та доцільність використання інформаційних технологій для аналізу взаємовпливу більшості конструктивно-технологічних параметрів процесів, що проходять у побутових твердопаливних котлах. Запропоновано інформаційну технологію дослідження процесів, що відбуваються у ТППК. Розглянуто загальний випадок процесу піролізного високотемпературного розкладання сировини рослинного походження, конструкцію та принцип роботи твердопаливного піролізного побутового котла. Запропоновано комплексну модель симуляції процесів високотемпературного піроліз- ного розкладання палива рослинного походження. Оскільки піролізне високотемпературне розкладання деревини з урахуванням теплообміну між потоками продуктів згоряння й теплоносієм є досить складним процесом, використано метод модульного моделювання. Першим етапом є двофазне горіння при нестачі кисню в камері газогенерації. Модель описує процеси горіння рідкого і твердого палива при дозвукових швидкостях течії газу. Другим етапом є однофазне горіння летких у камері згоряння. Моделі горіння летких обираються залежно від швидкості перебігу брутто- реакції. Третім етапом є моделювання процесу теплообміну між продуктами згоряння та теплоносієм у жаротрубному елементі, що базується на розв ’язку рівняння енергії з урахуванням радіаційної складової теплового потоку, Нав ’є- Стокса і рівняння для турбулентних функцій переносу. Результатом моделювання є епюри розподілу коефіцієнта надлишку повітря, температури та швидкостей на всіх етапах моделювання. Створена модель й отримані в результаті моделювання дані дають змогу встановити зв ’язок між конструктивно-технологічними параметрами ТППК та надати рекомендації щодо раціоналізації конструкції як існуючих побутових котлів, так і запропонувати нові конструктивні рішення. The usage of alternative and renewable energy sources is appropriate for energy sector of Ukraine. The paper is devoted to modeling the decomposition and combustion of plant raw materials processes in household solid-fuel boilers (HSFB). It is shown, that the efficiency of HSFB depends on a large extent of its operational and constructive parameters. The advantages and expediency of the use of information technologies for the analysis of the mutual influence of the majority of structural and technological parameters of processes which are taking place in household solid-fuel boilers are noted. An informational technology of research of processes occurring in HSFB is offered. A general case of the pyrolysis high-temperature decomposition of raw materials, construction and the principle of work of household solid-fuel boilers are considered. A complex model of simulation of high-temperature pyrolysis decomposition of plant fuels is proposed. Since pyrolytic high-temperature decomposition of wood, taking into account the heat exchange between combustion fluxes and coolant is a rather complicated process, the modular modeling method is used. The first stage is two- phase combustion with a lack of oxygen in the gas-generating chamber. The model describes the processes of combustion of liquid and solid fuel at subsonic gas flow rates. The second stage is the single-phase burning of volatiles in the combustion chamber. Volatile combustion models are chosen depending on the speed of the gross reaction. The third stage is the simulation of the heat exchange process between the combustion products and the coolant in a fire-cell element. The result of the simulation is the diagram of the distribution of the coefficient of oxygen excess, temperature and velocity at all stages of the simulation. The developed model and the data obtained in the simulation allow to establish the relationship between the technological and constructive parameters of the HSFB. It is also possible to provide recommendations on the rationalization of construction for existing household boilers and to propose new constructive solutions.The usage of alternative and renewable energy sources is appropriate for energy sector of Ukraine. The paper is devoted to modeling the decomposition and combustion of plant raw materials processes in household solid-fuel boilers (HSFB). It is shown, that the efficiency of HSFB depends on a large extent of its operational and constructive parameters. The advantages and expediency of the use of information technologies for the analysis of the mutual influence of the majority of structural and technological parameters of processes which are taking place in household solid-fuel boilers are noted. An informational technology of research of processes occurring in HSFB is offered. A general case of the pyrolysis high-temperature decomposition of raw materials, construction and the principle of work of household solid-fuel boilers are considered. A complex model of simulation of high-temperature pyrolysis decomposition of plant fuels is proposed. Since pyrolytic high-temperature decomposition of wood, taking into account the heat exchange between combustion fluxes and coolant is a rather complicated process, the modular modeling method is used. The first stage is two- phase combustion with a lack of oxygen in the gas-generating chamber. The model describes the processes of combustion of liquid and solid fuel at subsonic gas flow rates. The second stage is the single-phase burning of volatiles in the combustion chamber. Volatile combustion models are chosen depending on the speed of the gross reaction. The third stage is the simulation of the heat exchange process between the combustion products and the coolant in a fire-cell element. The result of the simulation is the diagram of the distribution of the coefficient of oxygen excess, temperature and velocity at all stages of the simulation. The developed model and the data obtained in the simulation allow to establish the relationship between the technological and constructive parameters of the HSFB. It is also possible to provide recommendations on the rationalization of construction for existing household boilers and to propose new constructive solutions.
Keywords: піроліз; горіння; синтез-газ; твердопаливні побутові котли; CFD-моделювання; коефіцієнт надлишку повітря; кафедра технологічного обладнання та комп’ютерних технологій проектування; pyrolysis; combustion; synthesis gas; household solid-fuel boilers; CFD-simulation; coefficient of oxygen excess